2003
DOI: 10.1097/01.aud.0000100204.08771.3d
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tinnitus in a Population of Older Adults: The Blue Mountains Hearing Study

Abstract: Interventions aimed at reducing age-related hearing loss, particularly by reducing excessive work-related noise exposure, and the effective, timely treatment of ear-related infections, may all decrease the risk of tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
171
5
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(205 citation statements)
references
References 31 publications
(28 reference statements)
17
171
5
9
Order By: Relevance
“…The incidence of tinnitus (64.4% and 72.5%, for men and women, respectively) in our study was higher when compared to other studies involving senior citizens (Rosenthall 20 to 42%; Nondahl, 5.7 to 8.2%; Sindhusake 30.3%) [32][33][34] . Such difference may be associated with the fact that we included in our study only elderly with one or more hearing complaints.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The incidence of tinnitus (64.4% and 72.5%, for men and women, respectively) in our study was higher when compared to other studies involving senior citizens (Rosenthall 20 to 42%; Nondahl, 5.7 to 8.2%; Sindhusake 30.3%) [32][33][34] . Such difference may be associated with the fact that we included in our study only elderly with one or more hearing complaints.…”
Section: Discussioncontrasting
confidence: 52%
“…In the study carried out by Nondahl et al 33 , prevalence varied between 5.7 and 8.2% of the elderly patients. Now, Sindhusake et al 34 studied 2015 elderly and they found a prevalence of 30.3%, and 48% of them had bilateral complaints, and only 6% received some treatment for this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Often, but not always, tinnitus is associated with a certain measure of hearing loss mostly of the upper part of the range of hearing (Henry et al, 1999). Hearing loss represents the most prevalent risk factor for tinnitus (Sindhusake et al, 2003; Moller, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Estimates suggest that approximately 10-14% of people in the general population and up to 30% of the subjects in a population aged 55 years and older report the presence of tinnitus [1,2]. hearing loss can be the basis for the selection of candidate genes.…”
Section: Introductionmentioning
confidence: 99%